Metal-organic frameworks for food contaminant adsorption and detection - Guo, Xueqi; Wang, Lili; Wang, Linjie; Huang, Qingzhen; Bu, Lijuan; Wang, Qiang (Frontiers in Chemistry, 2023)
Metal-organic framework materials (MOFs) have been widely used in food contamination adsorption and detection due to their large specific surface area, specific pore structure and flexible post-modification. MOFs with specific pore size can be targeted for selective adsorption of some contaminants and can be used as pretreatment and pre-concentration steps to purify samples and enrich target analytes for food contamination detection, thereby improving the efficiency of food contamination detection. In addition, MOFs, as a new functional material, provide an important way to develop new rapid detection methods that are simple, portable, inexpensive and with high sensitivity and accuracy. In this paper, we review Zn-based, Cu-based and Zr-based MOFs materials with low cost, easy access to raw materials and convenient synthesis conditions, discuss their applications in the adsorption and sensing detection of chemical and biological contaminants, respectively, and provide some ideas for future development.